Gd impurities effect on $$\hbox {Co}_{2}\hbox {CrSi}$$ Co 2 CrSi alloy: first-principle calculations - Yahiaoui, I.E.; Lazreg, Abbassia; Dridi, Z.; Al-Douri, Yarub; Bouhafs, Bachir (Indian Academy of Sciences, 2018)
First-principle calculations have been performed to study Gd impurities doping effect on the physical properties of the Heusler half-metallic ferromagnet Co 2CrSi using the density functional theory in the local spin density approximation with an additional Hubbard correlation term for the rare-earth 4f states. The results show that the gadolinium moment is aligned antiparallel to that of transition metal atoms for both Co 16Cr 7GdSi 8 and Co 15GdCr 8Si 8. The analysis of the doped material band structures shows that the half-metallic properties are completely conserved if Gd substitutes Cr atoms, while the minority-spin gap is filled and half-metallicity is lost when Gd substitutes Co atoms.